Progress on responsive neurostimulation in treatment of drug⁃resistant epilepsy - FAN Xiu⁃liang; BAI Yu⁃tong; YANG An⁃chao; ZHANG Kai (Chinese Journal of Contemporary Neurology and Neurosurgery)
Epilepsy is a common chronic neurological disorder that severely impacts the quality of life and social functioning. Approximately 1/3 of patients are diagnosed with drug⁃resistant epilepsy (DRE), for which conventional antiepileptic seizure medicine (ASM) and traditional surgery have limited efficacy. In recent years, responsive neurostimulation (RNS), as a closed⁃loop neuromodulation technique, has provided a novel treatment option for DRE. The RNS utilizes invasived electrodes to monitor brain activity in real time, detect seizure precursors, and deliver electrical stimulation, effectively reducing the frequency and severity of DRE. This paper aims to review the composition of the RNS, optimization and dyanmic adjustment of stimulation parameters, long⁃term data recording and analysis, fusion with machine learning, clinical efficacy, and comparison with vagus nerve stimulation (VNS). It also explores the technical challenges and discusses future development directions. RNS holds promise for providing personalized and precise treatment to more DRE and expanding its application to other neurological disorders.